2019
DOI: 10.1088/1361-6560/ab447c
|View full text |Cite
|
Sign up to set email alerts
|

Improving the modelling of susceptibility-induced spatial distortions in MRI-guided extra-cranial radiotherapy

Abstract: Magnetic-resonance linear-accelerator (MR-LINAC) systems integrating in-room magnetic-resonance-imaging (MRI) guidance are a currently emerging technology. Such systems address the need to provide frequent imaging at optimal soft-tissue contrast for treatment guidance. However, the use of MRI-guidance in radiotherapy should address imaging-related spatial distortions, which may hinder accurate geometrical characterization of the treatment site. Since spatial encoding relies on well-defined magnetic fields, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The susceptibility effects were attributable almost exclusively to the diamagnetic tissues, leading to a decrease of the overall magnetic field and a negative bias. 32 Overall, the implementation of the deformations into the CoMBAT phantom showed that deformations levels at the thoracic diaphragm can reach values up to 5 mm in fast MR sequences lacking 3D distortion correction. These effects can be effectively minimized by changing the MRI acquisition plane from axial to either sagittal or coronal, where the main motion direction (superior-inferior) can be sampled at better resolution and reduced distortion levels.…”
Section: C Implementation In the Combat Phantommentioning
confidence: 89%
See 4 more Smart Citations
“…The susceptibility effects were attributable almost exclusively to the diamagnetic tissues, leading to a decrease of the overall magnetic field and a negative bias. 32 Overall, the implementation of the deformations into the CoMBAT phantom showed that deformations levels at the thoracic diaphragm can reach values up to 5 mm in fast MR sequences lacking 3D distortion correction. These effects can be effectively minimized by changing the MRI acquisition plane from axial to either sagittal or coronal, where the main motion direction (superior-inferior) can be sampled at better resolution and reduced distortion levels.…”
Section: C Implementation In the Combat Phantommentioning
confidence: 89%
“…The magnitude of spatial distortions due to the use of the geometrical phantom for measurements was specifically evaluated, relying on the same susceptibility simulation algorithm used for the CoMBAT phantom. 32 A simulation was run at 1.5 T considering the presence of the PMMA phantom on the table support, including a thin layer of silica glue that was used to close the upper side of each phantom unit. Results show that average susceptibility-induced variations in the static magnetic field are in the micro-Tesla range, with corresponding deformations of −0.1 AE 0.3 mm in the z-direction at the minimum gradient strength of 9 mT/m, corresponding to the sGRE sequence.…”
Section: A Phantom Construction and Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations